EFFECTIVE INDEPENDENT LEARNING METHODS OF IMPLEMENTING INNOVATION AND INFORMATION TECHNOLOGIES IN THE EDUCATIONAL SYSTEM - Saytov Kamiljan Begdullaevich; Gayipbaev Nurlan Rakhmetovich (European Journal of Humanities and Educational Advancements, 2023)
From the point of view of modern teaching, the theory of innovative technologies is considered as an effective tool for students’ learning and cognitive activity regarding the problematic approach in education. Thus, the activation of teaching is, first of all, the organization of students’ actions aimed at finding solutions and solving specific learning problems in all academic subjects. Independent education means the organization of regular, independent and autonomous activity of the learning process in accordance with the subjective goal of the development of concepts, skills and competencies in an individual way. Therefore, teaching the general basics of the theory of educational technology in modern education, its laws, principles, purpose, content, tasks, objective and subjective factors, basic concepts and criteria with the help of information technology platforms